NMR-Based screening with competition water-ligand observed via gradient spectroscopy experiments: detection of high-affinity ligands. - Dalvit, C; Fasolini, M; Flocco, M; Knapp, S; Pevarello, P; Veronesi, M (2002)
Water-ligand observed via gradient spectroscopy (WaterLOGSY) represents a powerful method for primary NMR screening in the identification of compounds interacting with macromolecules, including proteins and DNA or RNA fragments. The method is useful for the detection of compounds binding to a receptor with binding affinity in the micromolar range. The Achille's heel of the method, as with all the techniques that detect the ligand resonances, is its inability to identify strong ligands with slow dissociation rates. We show here that the use of a reference compound with a known K(D) in the micromolar range together with properly designed competition binding experiments (c-WaterLOGSY) permits the detection of strong binders. A derived mathematical expression is used for the selection of the appropriate setup NMR experimental conditions and for an approximate determination of the binding constant. The experiment requires low ligand concentration, therefore allowing its application in the identification of potential strong inhibitors that are only marginally soluble. The technique is particularly suitable for rapid screening of chemical mixtures and plant or fungi extracts.